Earmarking Result Of Iease Smoke For The Service Of Health Of Society And Straightening Of Law - Minollah - (Unram Law Review, 2017)
Target of this writing is to study and analyse taxs earmarking in exploiting of Iease result smoke for the service of health society and straightening of law pursuant to Law Number 28 Year 2009 about Lease Area and Retribution Area by using approach of conceptual approach and legislation. Result of study were then analysed by using analysis of deskripsi qualitative with deductive reasoning and obtained conclusion that rule concerning earmarking result of Iease smoke more flange to earmarking symbolic, delivering usage of earmarking result of Iease smoke for the service of health society and straightening of law to taker of policy so that benefit of earmarking result of Iease smoke in service of health society and straightening of law still is unclear. Suggestion need dissociation of source defrayal of service of health society and straightening of law coming from Deconcentration fund and Duty aid, Special Fund Allocation of health area and Fund Sharing Holder Result of Duty Tobacco, with coming from cigarette Iease.